Endothelial Progenitor Cells in Diabetic Retinopathy - Lois, Noemi; McCarter, Rachel V.; O’Neill, Christina; Medina, Reinhold J.; Stitt, Alan W. (Frontiers in Endocrinology, 2014)
Diabetic retinopathy (DR) is a leading cause of visual impairment worldwide. Patients with DR may irreversibly lose sight as a result of the development of diabetic macular oedema (DMO) and/or proliferative diabetic retinopathy (PDR); retinal blood vessel dysfunction and degeneration plays an essential role in their pathogenesis. Although new treatments have been recently introduced for DMO, including intravitreal vascular endothelial growth factor inhibitors (anti-VEGFs) and steroids, a high proportion of patients ( 40-50%) do not respond to these therapies. Furthermore, for people with PDR laser photocoagulation remains a mainstay therapy despite this being an inherently destructive procedure. Endothelial progenitor cells (EPCs) are a low-frequency population of circulating cells known to be recruited to sites of vessel damage and tissue ischemia where they promote vascular healing and re-perfusion. A growing body of evidence suggests the number and function of EPCs is altered in patients with varying degrees of diabetes duration, metabolic control and in the presence of absence of DR. While there are no clear-cut outcomes from these clinical studies, there is mounting evidence that some EPC sub-types may be involved in the pathogenesis of DR and may also serve as biomarkers for disease progression and stratification. Moreover, some EPC sub-types have considerable potential as therapeutic modalities for DMO and PDR in the context of cell therapy. This review presents basic clinical concepts of DR and combines this with a general insight on EPCs and how they relate to future directions in understanding and treating this important diabetic complication.